Upaya Pencegahan Pernikahan Dini untuk Menyiapkan Generasi Ungul di Madrasah Aliyah Mambaul Ma’arif Belik - Abdulah; Ella Mubarokah; Khabibatun Asty Khanifah; Nila Anggraini; Rani Purniawanti (Program Studi Pendidikan Kimia FKIP Universitas Mataram, 2023)
Marriage is basically done to establish a harmonious relationship between men and women in a bond. The law has set the age of marriage at 19 years. However, the phenomenon of marrying under a predetermined age or commonly called early marriage is still common in Indonesia. This community service is carried out to provide education or counseling to MA Mambaul Ma'arif Belik students in Pemalang district regarding the prevention of early marriage, as well as provide an understanding of the impacts and risks of early marriage. This service is carried out using the lecture method (counseling) and question and answer with participants. The counseling went well and the participants consisting of students from grades X, XI and XII had high enthusiasm and participated in the question and answer session with the speakers.